Plasma and erythrocyte phospholipid fatty acid profile in professional basketball and football players - Tepsic, J.; Vucic, V.; Arsic, A.; Blazencic-Mladenovic, V.; Mazic, S.; Glibetic, M. (European Journal of Applied Physiology, 2009)
The effect of intensive long-term physical activity on phospholipid fatty acid (FA) composition has not been studied thoroughly. We determined plasma and erythrocyte phospholipid FA status of professional basketball and football players. Our results showed differences in plasma FA profile not only between sportsmen and sedentary subjects, but also between two groups of sportsmen. Plasma FA profile in basketball players showed significantly higher proportion of n-6 FA (20:3, 20:4, and 22:4) and total polyunsaturated FA (PUFA) than controls, while football players had higher palmitoleic acid (16:1) than basketball players and controls. Total PUFA and 22:4 were also higher in basketball than in football players. Erythrocyte FA profile showed no differences between football players and controls. However, basketball players had higher proportion of 18:0 than controls, higher saturated FA and lower 18:2 than two other groups, and higher 22:4 than football players. These findings suggest that long-term intensive exercise and type of sport influence FA profile